2018
DOI: 10.1016/j.bbadis.2017.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of aldosterone production by ion channels: From basal secretion to primary aldosteronism

Abstract: Aldosterone is produced by zona glomerulosa (ZG) cells of the adrenal cortex and plays a key role in balancing water and electrolytes levels. Autonomous overproduction of aldosterone leads to primary aldosteronism (PA), which is the most common form of secondary endocrine hypertension. Recently, significant progress has been made towards understanding the genetic basis of PA, where increasing clinical evidence suggests that mutations in ion channels appear to be the major cause of aldosterone-producing adenoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 136 publications
0
12
0
Order By: Relevance
“…Mutations in several genes encoding ion channels of ZG cells cause human PA 10,11,50 . Progress in understanding the underlying pathological mechanisms has been hampered by the absence of mouse models that faithfully replicate the human disease 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in several genes encoding ion channels of ZG cells cause human PA 10,11,50 . Progress in understanding the underlying pathological mechanisms has been hampered by the absence of mouse models that faithfully replicate the human disease 51 .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies indicate that the activity of the T-type, but not that of the L-type channel, correlates with aldosterone secretion in dispersed preparations of animal ZG cells and human adrenocortical cell lines (Barrett et al 1995, Rossier et al 1996b, Imagawa et al 2006, Akizuki et al 2008. Thus, surprisingly recent clinical studies have found more than 25 different somatic Ca V 1.3 L-type calcium channels mutations in patients with PA (Yang et al 2018), suggesting that in humans L-type calcium channels may also play an equally important role in controlling aldosterone production.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic hyperaldosteronism and aldosterone-producing adenoma are the two most common subtypes of PA (Funder et al 2008, Monticone et al 2017. Notably, somatic mutations of potassium and calcium channels have been found in more than half of aldosterone-producing adenomas (Yang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated ECF potassium promotes membrane depolarization in the adrenal zona glomerulosa, triggering voltage-dependent mechanisms that ultimately induce aldosterone release (Lotshaw, 2001;Yang et al, 2016Yang et al, , 2018. Aldosterone secretion requires a change in potassium current across the cell membrane (Yang et al, 2018), increasing roughly 100-fold per 1 mM rise in extracellular potassium (Lotshaw, 2001). In human patients, the importance of potassium for aldosterone release was solidified by the discovery that a frequent cause of primary hyperaldosteronism is a somatic KCNJ5 mutation that disrupts the potassium-selectivity of the Kir3.4 channel, allowing sodium entry through this channel to inappropriately depolarize aldosterone-secreting cells (Choi et al, 2011).…”
mentioning
confidence: 99%